2020
DOI: 10.1002/ptr.6703
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin effect on cancer cells' multidrug resistance: An update

Abstract: Chemotherapy is one of the main methods for cancer treatment. However, despite many advances in the design of anticancer drugs, their efficiency is limited due to their high toxicity and resistance of cells to chemotherapeutic drugs. In order to improve the cancer therapy, it is essential to use the compounds that can overcome drug resistance and increase treatment efficiency. Researchers have studied the effects of natural compounds for the controlling various drug resistance mechanisms. Curcumin is a natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 201 publications
(325 reference statements)
0
20
0
Order By: Relevance
“…CPG islands are abundant in the gene promoter region; methylation of these areas causes long-term silencing of genes [ 11 ]. It has been generally reported that hypomethylation in the oncogenes’ promoter increases their expression and hypermethylation in the tumor suppressor genes promoter causes the silencing of genes in many cancers [ 167 ]. Decreased expression of tumor suppressor genes has been shown to lead to increased plasticity in cell phenotype such as EMT, change in cell function, self-renewal and differentiation potential, and finally the formation of CSCs in different cancer cells [ 168 , 169 ].…”
Section: The Role Of Epigenetic Modifications In Cancer Stem Cells Resistance To Chemotherapy and Radiotherapymentioning
confidence: 99%
“…CPG islands are abundant in the gene promoter region; methylation of these areas causes long-term silencing of genes [ 11 ]. It has been generally reported that hypomethylation in the oncogenes’ promoter increases their expression and hypermethylation in the tumor suppressor genes promoter causes the silencing of genes in many cancers [ 167 ]. Decreased expression of tumor suppressor genes has been shown to lead to increased plasticity in cell phenotype such as EMT, change in cell function, self-renewal and differentiation potential, and finally the formation of CSCs in different cancer cells [ 168 , 169 ].…”
Section: The Role Of Epigenetic Modifications In Cancer Stem Cells Resistance To Chemotherapy and Radiotherapymentioning
confidence: 99%
“…Furthermore, Cur has been proved to have excellent safety and widespread availability with low cost. Previous studies have indicated that Cur can downregulate the NF-kB and PI3K/Akt signaling pathways in cancer cells, which can inhibit cell growth, induce apoptosis, and increase drug sensitization ( Hamzehzadeh et al, 2018 ; Subramaniam et al, 2018 ; Chen et al, 2019 ; Ghasemi et al, 2019 ; Maiti et al, 2019 ; Zusso et al, 2019 ; Borges et al, 2020 ; Keyvani-Ghamsari et al, 2020 ). In addition, the combination of PTX and Cur provided synergistic anti-cancer effects and eliminated cancer stem cells in TNBC ( Baek and Cho, 2017 ; Calaf et al, 2018 ; Saghatelyan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin reverses drug resistance mechanisms and results in increasing the sensitivity of chemotherapyresistant cells. In the research conducted by Keyvani-Ghamsari et al, they demonstrated that curcumin is an effective chemical in cancer treatment [85].…”
Section: Discussionmentioning
confidence: 99%